Influence of Emulsion Type and Moisture on the Stiffness of Stabilized Granular Soil - de Medeiros, Alexandre S.; da Silva, Marcelino A. V. (Salehan Institute of Higher Education, 2025)
The objective of this study is to investigate how moisture content affects the stiffness of a gravelly-sandy soil stabilized with asphalt emulsion, considering different types of emulsion (medium- and slow-setting) and modified compaction energy. Dynamic triaxial tests were carried out to determine the stiffness of specimens at different moisture contents, considering the dry and wet branches of the compaction curve, all stabilized with 2% asphalt emulsion. The influence of moisture content and emulsion type was assessed using robust analysis of variance (ANOVA), allowing the evaluation of statistical significance and the interaction between factors. The results showed that the stiffness of the stabilized soil is strongly influenced by moisture content, with a peak value observed near the optimum moisture ( 8.2%). The slow-setting (SS) emulsion achieved the best performance, reaching 938.94 MPa, representing a 452.32% increase compared to the untreated soil. The medium-setting (MS) emulsion also produced a significant stiffness gain (375.29%). Statistical analysis indicated that emulsion type was the most influential factor (Q = 1747; p = 0.001). This study contributes to the literature by experimentally and statistically demonstrating how moisture content and emulsion type affect the stiffness of stabilized soils.